2018
DOI: 10.1111/jfbc.12725
|View full text |Cite
|
Sign up to set email alerts
|

The nutraceutical potential ofLepidium sativum L.seed flavonoid-rich extract in managing metabolic syndrome components

Abstract: The present study aimed to investigate the phytochemical and pharmacological identities of a Lepidium sativum L. (LS) flavonoid‐rich extract and its beneficial effects on metabolic, hormonal, and histological status. Chemical screening, as well as high‐performance liquid chromatography with diode‐array detection (HPLC‐DAD) identified high concentrations of the main flavonoid compounds in LS crude extract such as flavonols (quercetin, kaempferol), flavones (luteolin, apigenin), and especially flavanones (naring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Biochemical and histopathological examinations revealed the protective effects of L. sativum flavonoid-rich extracts on high-fat diet-fed Wistar rats. They suggested that flavonoids could improve insulin sensitivity, dyslipidemia, inflammation, and pancreatic β cell viability [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Biochemical and histopathological examinations revealed the protective effects of L. sativum flavonoid-rich extracts on high-fat diet-fed Wistar rats. They suggested that flavonoids could improve insulin sensitivity, dyslipidemia, inflammation, and pancreatic β cell viability [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…The increase in mammogenic hormonal levels has been proven in animal models secondary to action of bioactive flavonoids on mammary glands. [ 5 ] The animal models prove that the treatment of L. sativum seeds leads to growing of the dimension of lobules and an abundance of vesicles[ 6 7 ] with branching dilated alveoli for all animals in virgins, pregnant, and lactating rats. There are quite a few animal studies of L. sativum where it has been evaluated in animal models producing excellent results.…”
Section: Discussionmentioning
confidence: 99%
“…It has a high nutritional value as it is also rich in iron and proteins and used in the postnatal period for new mother as it gives her strength and stamina which eventually increases the breast milk production. [ 5 ] The galactogoggue effect of Lepidium sativus seeds has not been quantified in randomized control trials in humans till date. In this context, we propose to study the galactogogeus effect of L. sativum seeds in postnatal mothers through an open-label non crossover trial.…”
Section: Introductionmentioning
confidence: 99%
“…34 Rich amounts of flavonoids present in the L. sativum extract increase insulin sensitivity, inflammation, pancreatic cell integrity, and dyslipidemia. 35 Researches reveal that garden cress seeds contain trace elements that have antidiabetic properties. 36 Lepidine, semi-lepidine, and imidazole alkaloids found in L. sativum seeds also have an anti-diabetic effect by increasing the amount of insulin secreted by the surviving islet -cells in the pancreas.…”
Section: Anti-diabetic Propertymentioning
confidence: 99%